The Influence of Digitalization in Encouraging Crime: A Criminological Perspective - Balqis, Ainun Agustina Atiqah; W. Badu, Lisnawaty (Estudiante Law Journal, 2025)
Digitalization has a significant impact on the increase in crime, especially through the phenomenon of criminal imitation models spread on the internet. This research aims to analyze the influence of digitalization on crime from a criminological point of view. The methodology used is a qualitative approach with a descriptive design and normative data collection techniques. The results showed that the development of digitalization triggered an increase in imitative criminal behavior, as shown by police data indicating an upward trend in crime in the last five years. Social media, especially TikTok, is the main platform for disseminating content that encourages imitation of criminal acts. These findings confirm the importance of strengthening regulations and prevention strategies to mitigate the negative impact of digitalization on criminal behavior